2018
DOI: 10.1194/jlr.m084947
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic importance of adipose tissue monoacylglycerol acyltransferase 1 in mice and humans

Abstract: Adipocyte triglyceride storage provides a reservoir of energy that allows the organism to survive times of nutrient scarcity, but excessive adiposity has emerged as a health problem in many areas of the world. Monoacylglycerol acyltransferase (MGAT) acylates monoacylglycerol to produce diacylglycerol; the penultimate step in triglyceride synthesis. However, little is known about MGAT activity in adipocytes, which are believed to rely primarily on another pathway for triglyceride synthesis. We show that express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 28 publications
(32 reference statements)
4
45
0
Order By: Relevance
“…A limitation of the current study is that the ASO targeting Mogat1 leads to diminished expression of this enzyme systemically (mainly liver and adipose tissue) rather than a tissue-specific manner. This may be important because we have recently shown that Mogat1 is robustly induced in adipocytes during differentiation and is involved in reesterifying fatty acids to prevent their efflux from these cells (35). There are several points that suggest that the present observations are not due to adipose effects of the ASO.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A limitation of the current study is that the ASO targeting Mogat1 leads to diminished expression of this enzyme systemically (mainly liver and adipose tissue) rather than a tissue-specific manner. This may be important because we have recently shown that Mogat1 is robustly induced in adipocytes during differentiation and is involved in reesterifying fatty acids to prevent their efflux from these cells (35). There are several points that suggest that the present observations are not due to adipose effects of the ASO.…”
Section: Discussionmentioning
confidence: 68%
“…There was also no observed effect of the Mogat1 ASO on plasma FFAs, MAG concentration, or the relative abundances of several species of lipids. Lastly, our previous work has suggested that the effects of adipocyte MGAT activity on fatty acid retention is most important in the fed state and does not affect lipolytic flux in the fasted state (35). Nonetheless, we cannot exclude the possibility that depletion of Mogat1 in adipose tissue by the ASO does not factor into the phenotype of our mice.…”
Section: Discussionmentioning
confidence: 85%
“…However, adipocyte proliferation rates, determined in vivo by measurement of the incorporation of ingested deuterium into the DNA of adipocytes isolated from SAAT, have been reported as either not different (106) or lower (107) in people who were overweight/obese and insulin sensitive than in people who were overweight/obese and insulin resistant. The capacity for lipogenesis in SAAT, assessed as expression of genes involved in lipogenic pathways (CD36, GLUT4, ChREBP, FASN, and MOGAT1), is greater in people with MHO than MUO (101,102,108,109). Moreover, the expression of these genes is positively correlated with insulin sensitivity (108,109), and increases more after moderate weight gain in people with MHO than MUO (110).…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…The capacity for lipogenesis in SAAT, assessed as expression of genes involved in lipogenic pathways (CD36, GLUT4, ChREBP, FASN, and MOGAT1), is greater in people with MHO than MUO (101,102,108,109). Moreover, the expression of these genes is positively correlated with insulin sensitivity (108,109), and increases more after moderate weight gain in people with MHO than MUO (110). Collectively, these data refute the notion that impaired adipogenesis contributes to insulin resistance in people with MUO (111), but demonstrate that increased adipose tissue gene expression of lipogenic pathways is associated with metabolic health.…”
Section: Review Series: Mechanisms Underlying the Metabolic Syndromementioning
confidence: 99%
“…Mogat1 expression is induced during adipogenesis. Mogat1 plays an important role in adipocyte differentiation by contributing to the production and accumulation of triglycerides by catalyzing the conversion of mono-acylglycerides to di-acylglycerides, which are subsequently converted to tri-acylglycerides 66 . The correlation between Nnat and Mogat1 is non-linear, which supports our proposed model that Nnat affects Mogat1 by regulating activation of CREB.…”
Section: Discussionmentioning
confidence: 99%